2017
DOI: 10.1038/ncomms15671
|View full text |Cite
|
Sign up to set email alerts
|

Age-related delay in visual and auditory evoked responses is mediated by white- and grey-matter differences

Abstract: Slowing is a common feature of ageing, yet a direct relationship between neural slowing and brain atrophy is yet to be established in healthy humans. We combine magnetoencephalographic (MEG) measures of neural processing speed with magnetic resonance imaging (MRI) measures of white and grey matter in a large population-derived cohort to investigate the relationship between age-related structural differences and visual evoked field (VEF) and auditory evoked field (AEF) delay across two different tasks. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 60 publications
5
60
0
Order By: Relevance
“…Although feature representation was qualitatively similar across young and older adults, it was delayed by 40 ms and weaker in older adults, in the absence of generic delays in the onset of visual cortical activity in older participants. This suggests that the reported delay occurred at the stages of cortical information processing, and was not due to precortical neural factors; thereby adding to the evidence that processing speed delays are unlikely to be due to bottom‐up optical factors, such as senile miosis, contrast sensitivity (Bieniek, Bennett, Sekuler, & Rousselet, ; Bieniek, Frei, & Rousselet, ), or visual acuity (Price et al, ). Furthermore, we believe that bottom‐up optical factors were unlikely contributors to the observed differences at the neural level, because any bottom‐up factors should affect all neural responses irrespectively of their category, whereas we observed much larger N170 to noise textures in older than in young participants.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Although feature representation was qualitatively similar across young and older adults, it was delayed by 40 ms and weaker in older adults, in the absence of generic delays in the onset of visual cortical activity in older participants. This suggests that the reported delay occurred at the stages of cortical information processing, and was not due to precortical neural factors; thereby adding to the evidence that processing speed delays are unlikely to be due to bottom‐up optical factors, such as senile miosis, contrast sensitivity (Bieniek, Bennett, Sekuler, & Rousselet, ; Bieniek, Frei, & Rousselet, ), or visual acuity (Price et al, ). Furthermore, we believe that bottom‐up optical factors were unlikely contributors to the observed differences at the neural level, because any bottom‐up factors should affect all neural responses irrespectively of their category, whereas we observed much larger N170 to noise textures in older than in young participants.…”
Section: Discussionmentioning
confidence: 73%
“…Although feature representation was qualitatively similar across young and older adults, it was delayed by 40 ms and weaker in older adults, in the absence of generic delays in the onset of visual cortical activity in older participants. This suggests that the reported delay occurred at the stages of cortical information processing, and was not due to precortical neural factors; thereby adding to the evidence that processing speed delays are unlikely to be due to bottom-up optical factors, such as senile miosis, contrast sensitivity (Bieniek, Bennett, Sekuler, & Rousselet, 2016;Bieniek, Frei, & Rousselet, 2013), or visual acuity (Price et al, 2017). Although our stimuli were only frontal views of faces, it would be interesting to test side views, in line with previous studies showing age-related behavioral decrement on perception of faces across viewpoints (Habak, Wilkinson, & Wilson, 2008;Wilson, Mei, Habak, & Wilkinson, 2011).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…peak evoked latency Sensory processing may slow down in the course of aging (Price et al, 2017). Here, we assessed the evoked response latency during auditory, visual and simultaneous audiovisual stimulation (index 1, Table 3).…”
Section: Meg Featuresmentioning
confidence: 99%
“…source reconstruction. It has been shown that these 31 methods can be cast into the generalised model 32 s(t) = C s L C −1 x(t) =: w x(t) (2) where C ∈ R N ×N is the sensor covariance matrix, C s ∈ R M ×M is the source 33 covariance matrix,ŝ is the estimated source amplitude (a.k.a. virtual channel), and 34 w ∈ R N is the spatial filter [12].…”
mentioning
confidence: 99%